2021
DOI: 10.1039/d1ma00426c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gate effects observed in fluoroalkylsilane self-assembled monolayers grafted on LiNi0.5Mn1.5O4cathodes: an application to efficient ion-exchange reactions

Abstract: We demonstrated the role of fluoroalkylsilane (FAS) self-assembled monolayers in improving the high-voltage durability and C-rate capabilities of spinel LiNi0.5Mn1.5O4 (LNMO) cathodes. The influence of the cathode–electrolyte interface (CEI) layer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Li + ions are likely to be easily penetrating between fluoroalkyl chains (CF 2 ) due to their small ionic radius (≈90 pm, 6-coordination number) and are strongly trapped at CF bonds due to a high charge density of Li + ion. [58][59][60] Cs + ions, however, are less likely to penetrate between fluoroalkyl chains because of their larger ionic radius (≈181 pm). Also, coulombic attraction between Cs + ions and CF bonds is much weaker than between Li + ions and CF bonds because of a low charge density of Cs + ion.…”
Section: Resultsmentioning
confidence: 99%
“…Li + ions are likely to be easily penetrating between fluoroalkyl chains (CF 2 ) due to their small ionic radius (≈90 pm, 6-coordination number) and are strongly trapped at CF bonds due to a high charge density of Li + ion. [58][59][60] Cs + ions, however, are less likely to penetrate between fluoroalkyl chains because of their larger ionic radius (≈181 pm). Also, coulombic attraction between Cs + ions and CF bonds is much weaker than between Li + ions and CF bonds because of a low charge density of Cs + ion.…”
Section: Resultsmentioning
confidence: 99%
“…R/Si = 2 corresponds to a singlering polysiloxane structure with a low polymerization degree (4) and high-molar-mass linear polysiloxane (5). R/Si < 2 refers to network polymer (6), condensed ring (7), spiro (8), spherical ring (9) polysiloxanes with different crosslinking degrees and also T-shaped polysiloxane (10). [41] Such a variety of siloxane functionalization and molecular configuration implies special versatility and multiple energy applications (Scheme 2).…”
Section: Structure Of Siloxanementioning
confidence: 99%
“…For example, Zettsu and co‐workers reported that spinel LiNi 0.5 Mn 1.5 O 4 (LNMO) cathodes modified by fluoroalkylsilane (FAS) monolayers showed improved C‐rate capabilities and high voltage durability. The FAS layer grafted on electrode surface effectively facilitated the Li + exchange reaction and eliminated the oxidative decomposition of free‐carbonate solvents by preferentially permeating solvated Li + /PF 6 − ions and blocking solvents from the cathode surface, respectively [10] …”
Section: Introductionmentioning
confidence: 99%
“…The FAS layer grafted on electrode surface effectively facilitated the Li + exchange reaction and eliminated the oxidative decomposition of freecarbonate solvents by preferentially permeating solvated Li + / PF 6 À ions and blocking solvents from the cathode surface, respectively. [10] In addition, the wide application of siloxanes as functional solvents, [11] co-solvents, [12] or additives [13] for electrolytes can promote the cell performance because they satisfy one or more of the following prerequisites. [14] Siloxanes display: 1) High ionic conductivity; 2) High thermal and chemical stability; [15] 3) Wide electrochemical window to maintain the stability of electrochemical performance over a wide voltage range.…”
Section: Introductionmentioning
confidence: 99%